Emotional Reading of the Story "Među zverima" by Mihajlo Pantić - Piskač, Davor (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The aim of the paper is to demonstrate how emotional or/and therapeutic reading enables readers to become aware of their own emotions through interaction with a literary text, making literature a tool for emotional growth and development. Therapeutic reading is introduced as a novel approach, distinct from aesthetic or purely entertainment-focused reading. It emphasizes the pragmatic, bibliotherapeutic functions of a text, setting it apart from traditional literary criticism. This method centers on the emotions evoked in the reader by a text and employs techniques such as understanding conceptual emotional metaphors, symbolic modeling, and the MED cycle, rooted in cognitive psychotherapy.Furthermore, the paper highlights the importance of viewing emotions as symbolically generalized communication media, which bridge the literary system and the reader’s psychological system. These concepts are exemplified through a bibliotherapeutic analysis of Mihajlo Pantić’s story Među zverima (Among the Beasts), chosen for its suitability to therapeutic reading due to the clear connections between the protagonist’s thoughts, emotions, and life decisions—precisely the focus of therapeutic reading.Additionally, the paper outlines the essential qualities required for a facilitator of therapeutic reading to ensure the process is both functional and ethical.
Keywords: Mihajlo Pantić; emotional (therapeutic) reading; conceptual metaphor; symbolic modeling; MED cycle